Exploring the Determinants of Liquidity of Private Commercial Banks in Bangladesh: Moderating Effect of Bank Age - Hoque, Md. Amdadul; Akter, Ripa; Begum, Fahmida (Finance & Economics Review, 2025)
Purpose: The main objective of this study is to explore the critical bank-specific determinants of the liquidity of private commercial banks in Bangladesh. Methods: This research examined the financial statements of twenty private commercial banks in Bangladesh over thirteen years (2010–2022). Various statistical tests and analyses, including the F-test, Breusch and Pagan LM Test, Modified Wald Test, Pesaran CD Test, Wooldridge Test, and Feasible GLS Model, were employed to evaluate the panel data. Results: The regression results showed that the net interest margin, capital adequacy, financial leverage, credit quality, operating efficiency, and bank age are statistically significant variables influencing the liquidity of private commercial banks in Bangladesh. The study also indicates that a bank`s age moderates the impact of financial leverage, credit quality, and operating efficiency on liquidity. Implications: The study’s theoretical implications deepen understanding of factors influencing bank liquidity, integrating bank age as a moderating variable. As far as the practice is concerned, it assists policymakers and bank managers in enhancing liquidity management techniques, guaranteeing financial stability, and promoting resilience within the banking industry. Originality: This study distinguishes itself by examining the moderating effect of bank age on liquidity determinants in private commercial banks in Bangladesh, a facet seldom explored in prior studies.